Correction of Intensity of Bone Involvement (IBI) Index by Lean Body Mass and Body Surface Area - Monteiro Bianchi J. Santos, Giovanna; Seren Takahashi, Maria Emilia; Mosci, Camila; P. M. Souza, Stephan; de Souza , Carmino Antonio; G. H. Lorand-Metze, Irene; Barreto Campello Carvalheira, José; Ramos , Celso Darío (Revista Brasileira de Física Médica, 2024)
The Intensity of Bone Involvement (IBI) parameter is utilized to quantitatively assess bone involvement in PET/CT images of multiple myeloma (MM) patients, providing an objective and reproducible analytical approach. This study proposes the mathematical correction of IBI for lean body mass (LBM) and body surface area (BSA) in 18F-FDG PET/CT images of MM patients. Beyond the corrections, our aim is to evaluate the correlation of corrected IBIs and visual image analysis, along with their relationship with overall patient survival. Methods: This retrospective study analyzed 18F-FDG PET/CT images and clinical data from 73 MM patients. LBM was calculated using the James and Janma models, while BSA was calculated using the DuBois model. The conventionally calculated IBI parameter was then corrected for LBM and BSA. Three experienced nuclear medicine physicians visually classified the intensity of bone involvement as: negative, mild, moderate, marked, and very marked. We compared standard IBI and corrected indices with visual classification using Kruskal-Wallis test and Dunn’s post-hoc test. Cox proportional hazards regression analysis was employed to test the association with overall patient survival. Statistical significance was established for p-values <0.05. Results: A positive relationship was observed between both standard IBI and its corrected values with visual image classification. No statistically significant association was found between IBI values and overall patient survival. Conclusions: IBI corrected for both LBM or BSA exhibited similar performance to standard IBI compared to visual image classification. However, IBI values (both standard and its corrections) were not associated with overall survival (OS) in our study.